Nutrition in the European Commission's external assistance: Third progress report on the nutrition action plan - International Food Policy Research Institute (2018)
Session Presentation IFPRI-FAO conference side event, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand